Imaginarios y prácticas de participación ciudadana para el control de la gestión pública - Muñoz Contreras, Luis Rodrigo (2015)
This research identifies the imaginary and present practices around the citizen participation in public management control to determine those that facilitate this task, or conversely, the more difficult. Presumably this relationship otherness between these two subjects occurs, and will be important in the context of imaginary identified, reflect on this otherness, ie analyze the anthropological question proposed Krotz, one of the authors what this research is based; This is complemented by analyzing the density or social citizenship status given by Aquín (2003). To identify the mentioned elements are part of a theoretical route posed subjects are carriers of needs and capabilities that have to be met and developed respectively; for which they require social conditions: material, cultural and good governance. These conditions have to be built in co-responsibility by the State and citizens, the latter from the social control. It is through this route that these imaginary and practices to reflect on the anthropological question are identified, however, to have the necessary and sufficient elements, field work was aimed to investigate the interviewed some key aspects: how mean the rights issue (meaning, experiences, conditions for exercising rights, effect of exercise of rights); how mean the social control of public management; and how they look at themselves and how they look on the other, in the context of control practices of governance.